Determination of codling moth, Cydia pomonella (Lep.: Tortricidae), generation numbers and adult population fluctuation in Yasouj through two different methods - Mohammadi, Hojjatollah (Acta entomologica slovenica (Ljubljana), 2016)
Population fluctuation of adult codling moth was studied in Yasouj through two methods, (1) sex pheromone-baited trapping and (2) collecting of larvae and maintaining them in natural conditions, to determine its appropriate spraying time. In the first method, three generations of adults emerged from mid-April to early June (45 days), late May to mid-July (60 days) and mid-July to mid-September (60 days). Their flight peaks occurred after mid-April, after mid-June and early August. At the time of flight peak, second and third generation adult populations were equal but twice as high as first generation adult population. In the second method, three generations of adults emerged during April (25 days), early June to mid-July (45 days) and mid-July to late August (45 days). Their flight peaks occurred in mid-April, mid-June and end July. Both methods were congruent for showing population fluctuation. Flying periods of the second and third generations were equal but longer than flying period of the first generation. Flying periods in the second method were shorter than flying periods in the first method. Flight peaks of both methods coincided but with slight delay for the first method. Some of first generation larvae remained dormant for one year and emerged as adults next year which shows that some individuals were monovoltine. Spraying time for the study area can be adjusted according to the findings of this study and the type of pesticide which have to be used.
Keywords: codling moths; Cydia pomonella; Iran; jabolčni zavijači; Lepidoptera; metulji; monitoring; population fluctuation; Tortricidae; Yasouj